ANALISIS SK DAN KD PADA STANDAR ISI MATA PELAJARAN BAHASA INDONESIA DI SD BERDASARKAN KETERAMPILAN BERBAHASA, ILMU KEBAHASAAN, DAN ILMU KESASTRAAN (Analisis isi SK dan KD Mendengarkan, Berbicara, Membaca, dan Menulis) - Aan Sugiantomas; Mahpudin Mahpudin (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
Standard contents is government job result for education unit and then developed by each education unit. in standard contents consist of standard competence and competence base that include listening, speaking, reading, and writing skill with linguistic science that include about fonology, morphology, syntax, and semantic, also literature science that include about, poetry, fiction prose, and drama. Begining from that, the author want to analyze how far matter scope between language skill, linguistic science, and literature science. Based on research result about SK and KD in standard indonesian subject contents at SD seen from know-how speaks, obvious that has sequence highest know-how speaks, seen from linguistic science, obvious that has sequence highest science semantic linguistic, and seen from literature science, obvious that has sequence highest science poetry literature. Keywords: analysis, Indonesian, skills, literature, content standards.